2020
DOI: 10.1016/s2468-2667(20)30145-6
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use among adults in China: findings from repeated cross-sectional surveys in 2015–16 and 2018–19

Abstract: Background The use of e-cigarettes among adults is increasing globally. Since 2018, policies in China have restricted e-cigarette use; however, little information is available on the national trend in e-cigarette use before regulations were implemented. Therefore, we sought to estimate the trend in e-cigarette use in China before policy implementation and explored associated factors. MethodsWe assessed two nationally representative cross-sectional datasets from the China Chronic Disease and Nutrition Surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 21 publications
2
53
0
2
Order By: Relevance
“…Although the role of e-cigarettes in smoking cessation is still a controversial public health issue, e-cigarettes are increasingly popular worldwide, especially among youth [6][7][8][9] . In the United States, rates of e-cigarette use surpassed those of cigarettes among youth in 2014 2 , and e-cigarette use is a national epidemic with high prevalence among high school and middle school students (27.5% and 10.5%, respectively) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of e-cigarettes in smoking cessation is still a controversial public health issue, e-cigarettes are increasingly popular worldwide, especially among youth [6][7][8][9] . In the United States, rates of e-cigarette use surpassed those of cigarettes among youth in 2014 2 , and e-cigarette use is a national epidemic with high prevalence among high school and middle school students (27.5% and 10.5%, respectively) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, what we know is that there is a sharp increase in the initiation of EC use among the youth and young adults, 54 whilst another study reported an increase in EC use among adults in general. 2 Therefore, the factors leading to this increase need to be studied more extensively. The findings from this study suggest that those exposed to promoting messages regarding EC use in conventional media minimized its addictiveness, whilst those receiving harmful messages in both social and conventional media believed that EC users were less socially acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, studies from population data had established that electronic cigarette (EC) use has increased rapidly and gained popularity in recent years. 1 , 2 A study in China reported an increasing prevalence of EC use among adults in general, 2 whilst another study reported an increase in prevalence among young adults but did not increase among middle-aged and older adults. 3 An upward trend was also indicated in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…12 ENDS use is less common in Asia than in these other regions, with current use around 1.8% in China. 13 ENDS also have emerged in South African market. [14][15][16] ENDS use prevalence is even lower in some low and middle-income countries (LMICs) such as Bangladesh and Zambia.…”
Section: Electronic Nicotine Delivery Systemsmentioning
confidence: 99%